Analysis on the adjustment of transportation structure and the logistics transformation of railway freight - Chaohe Rong; Xingchan Li; Gaiping Zhang; Xuecheng Wang (Railway Sciences)
Purpose – This paper aims to provide a comprehensive analysis of the strategic adjustments in China's transportation structure, with a particular focus on the pivotal role of railway freight and its integration into the modern logistics system. It seeks to address the need for a more nuanced understanding of the “road to rail” policy, emphasizing the importance of intermodal collaboration and service of fragmented market demands. Design/methodology/approach – The study employs a transport economics perspective to evaluate the achievements and shortcomings of China's transportation structure optimization. It bases its assessment of the current state of railway freight logistics, multi-modal transportation and the broader implications for the transportation service market on data analysis. The methodology includes a review of existing policies, an examination of industry practices and a comparative analysis with global trends in railway logistics. Findings – The research underscores the importance of focusing on the development of non-bulk materials, noting the insufficiency in the development of China's rail multi-modal transportation and highlighting the instructive value of successful cases in open-top container road-rail intermodal transportation. The study posits that the railway sector must enhance cooperation with other market entities, aligning with the lead enterprises in the logistics chain that are characterized by speed, high value and strong coordination capabilities, in order to better serve the transportation market. This approach moves away from a reliance on the railway's own capabilities alone. Originality/value – This paper offers original insights into the transformation of railway freight in China, contributing to the body of knowledge on transportation economics and logistics. It provides valuable recommendations for policymakers and industry practitioners, emphasizing the strategic importance of railway logistics in the context of China's economic development and intense competition in the supply chain. The value of the article lies in its comprehensive understanding of the complexities involved in the adjustment of transportation structures, providing direction for the market-oriented reform of China's railway freight sector.